Interesting Botryosphaeria (Botryosphaeriaceae) associated with Magnolia species in Thailand: Additions of two new host records with their lifestyles - de Silva, Nimali I.; Phillips, Alan J.l.; Tennakoon, Danushka S.; Kumla, Jaturong; Suwannarach, Nakarin; Lumyong, Saisamorn (Phytotaxa, 2023)
Botryosphaeria is a commonly encountered and economically important genus whose species are widely distributed phytopathogens as well as endophytes, necrotrophs and saprobes. We herein provide insights into botryosphaeriaceous microfungi associated with Magnolia species in Thailand. Phylogeny based on combined ITS, tef1 and tub2 sequences coupled with their morphological characteristics verified the status of the new collection as new host records of Botryosphaeria kuwatsukai and B. puerensis from Magnolia species. Prior to this investigation, only a few Botryosphaeria species have been discovered in Thailand. This is the first account of B. kuwatsukai from Magnolia species as well as the first geographical record in Thailand. Furthermore, we reveal endophytic and saprobic B. puerensis in Thailand for the first time and its first association with Magnolia species. Along with the host associations and geographic distributions, we also emphasized the lifestyles of Botryosphaeria species that are used in the current phylogenetic analyses.